OPTIMASI KONSENTRASI PELARUT ETANOL DAN SUHU EKSTRAK DAUN TURI PUTIH (Sesbania grandiflora L.) DENGAN METODE UAE TERHADAP AKTIVITAS ANTIOKSIDAN SECARA FACTORIAL DESIGN - Ghani Nurfiana Fadma Sari; Shella Juana Putri; Nuraini Harmastuti (Fakultas Farmasi Universitas Setia Budi, 2025)
White Turi leaves (Sesbania grandiflora L.) are widely recognized as ornamental plants and vegetables and are known for their antioxidant properties due to their content of various secondary metabolites, such as alkaloids, saponins, tannins, flavonoids, and terpenoids. This study aimed to optimize solvent concentration and extraction temperature using the ultrasound-assisted extraction (UAE) method and to investigate the antioxidant activity of white turi leaf extracts using a factorial design approach. The UAE method was employed for the extraction process with ethanol concentrations of 70% and 96% and extraction temperatures of 45°C and 50°C as experimental factors. The responses observed included the extraction yield of white turi leaf extract and antioxidant activity expressed as IC₅₀ values. The results revealed that an ethanol concentration of 96% at an extraction temperature of 50°C produced the highest extraction yield of 18.66%. The highest antioxidant activity was observed using 70% ethanol at 45°C, with an IC₅₀ value of 18.86 µg/mL. Based on the factorial design analysis, an ethanol concentration of 70% combined with an ultrasonic extraction temperature of 45°C was selected as the optimal extraction condition for achieving a favorable balance between extraction yield and antioxidant activity.